Interactive effects of extreme temperature and a widespread coastal metal contaminant reduce the fitness of a common tropical copepod across generations. (October 2020) - Dinh, Khuong V.; Nguyen, Quyen T.T.; Vo, Thi-My-Chi; Bui, Trung Ba; Dao, Thanh-Son; Tran, Duc M.; Doan, Nam X.; Truong, Trinh S.H.; Wisz, Mary S.; Nielsen, Torkel Gissel; Vu, Minh T.T.; Le, Minh-Hoang
Abstract: Tropical coastal areas are increasingly exposed to temperature extremes from marine heatwaves and contaminants from anthropogenic activities. The interactive effects of these environmental changes on marine life are understudied. We investigated the direct and cross-generational effects of copper (Cu) on F0 and F1 generations of the common tropical copepod Pseudodiaptomus annandalei under extreme temperatures (30 and 34 °C). In F0, Cu exposure reduced survival and nauplii production; these patterns were more pronounced at 34 °C and in females. F0 Copepods produced more faecal pellets at 34 °C than 30 °C, indicating a higher energetic demand. In F1, the number of F1 adults was lower in CuF0 and at 34 °C. Cu-exposed F0 produced larger adult F1, while exposure to 34 °C resulted in smaller adult F1. Our results show that tropical copepods are highly vulnerable to the interactive effects of contaminants and extreme temperatures. Graphical abstract: Unlabelled Image Highlights: Tropical copepods are assumed to be highly vulnerable to pollutants and warming. Tropical copepod Pseudodiaptomus annandalei was exposed to Cu and temperature. Cu reduced survival and nauplii production, especially at higher temperature. In F1, the number of F1 adults was lower in Cu-F0 and at 34 °C. Potential cascading effects on the entire tropical coastal food web